The American heiress : a novel - Goodwin, Daisy (New York : St. Martin's Press, 2010)
Traveling abroad with her mother at the turn of the twentieth century to seek a titled husband, Cora Cash suddenly finds herself Duchess of Wareham, married to Ivo, the most eligible bachelor in England. Nothing is quite as it seems, however: Ivo is withdrawn and secretive, and the English social scene is full of traps and betrayals. Money, Cora soon learns, cannot buy everything, as she must decide what is truly worth the price in her life and her marriage.
Originally published as: My last duchess.
Keywords: Americans -- England -- Fiction; Aristocracy (Social class) -- England -- Fiction; England -- Social life and customs -- 19th century -- Fiction